Career Locus of Control and School- and Career-Related Adjustment Among High-Need Youth With and Without Disabilities. (October 2019) - Pham, Yen K.; Murray, Christopher
An internal locus of control has benefits to individuals across multiple life domains, but little is known about associations between career locus of control (CLOC) and adjustment outcomes for adolescents with disabilities or at risk of academic failure. This exploratory study used data from 252 high school students to examine associations between CLOC and indicators of school- and career-related adjustment for high-need youth. Findings indicated that an internal CLOC contributed significantly to explaining variances in school bonding, engagement, career self-efficacy, and outcome expectations. Results also showed that adolescent girls with disabilities scored higher on external CLOC compared to boys with disabilities and boys and girls without disabilities. However, there were no moderation effects of ability status or gender on the strengths of CLOC and adjustment associations. Implications for research and practice were discussed in the context of study limitations.